Przymus adwokacko-radcowski w postępowaniu karnym - Sikorski, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the article is to discuss the institution of an advocate in criminal proceedings. It occurs in the event of an indictment by a subsidiary of the victim, as well as for the preparation and signing of an appeal against the judgment of the district court, moreover, in the case of appeal from a final judgment of the Supreme Court and in the case of an application for reopening of the criminal proceedings, and also in the case of a complaint to the judgment of the appellate court.
Keywords: adwokat; obligatoryjna pomoc adwokata (adwokat przymusowy); postępowanie karne